Social determinants of vulnerability to ill-health: Evidences from Mendi Town, Western Ethiopia - Amanti Baru; Padmanabhan Murugan (Journal of Health and Social Sciences)
Introduction: The premise of this study is that disparity in individuals’ degree of susceptibility to physical and mental ill-health is determined by the amount of structurally (socially) distributed resources (‘capitals’). Based on Pierre Bourdieu’s theory of capitals, the study identified and employed economic, social and cultural capitals acting as structurally distributed resources that determine the health outcomes of people in Ethiopia. Methods: This study used a cross-sectional survey design to collect quantitative data from 276 randomly selected respondents in Mendi Town, Western Ethiopia to ascertain the role of capitals in determining individuals’ level of vulnerability to physical and mental ill-health. Moreover, qualitative data collected through in-depth interviews, focus group discussions, and key informant interviews have been used to deeply understand the pathways in which ‘capitals’ affect health outcomes. Results: Our study revealed that inequality in the level of vulnerability to ill-health among individuals across different social-strata is based on unequal distribution of capitals. The study found that the poorest individuals, women, elderly, widowed, divorced, and individuals with poor education are the most vulnerable groups to ill-health in the study area. These groups are deprived of adequate economic, social, and cultural capitals that would enable them to avoid ill-health. Majority of the study population are highly vulnerable to ill-health and they are found to have poor health status due to deprivation of capitals. Nevertheless, only little targeted interventions have been made to increase the levels of capitals available for people and to enhance their health status. Conclusion: This study is aligned with an economic perspective of the social determinants of health; it showed that social factors are fundamental agents for protecting individuals from ill-health or to make them vulnerable. The authors recommend public health interventions that consider the social context of individuals in order to reduce vulnerability to ill-health and improve their health status.